Construction Strategies of Rural Residential Management Data Platform—A Case Study of Crystal Town Residence in Pingwu County, Mianyang. Issue 6 (June 2020) - Mei, Wu; Dan, He
Abstract: There are large numbers and areas of rural dwellings in China. Because of remote locations of many villages or improper protections of local residents, countless historical villages and traditional dwellings are gradually disappearing. Digital information platforms will preserve data of residential buildings through professional surveys and mappings, which timely and effectively integrate all kinds of residential information, share data to the maximum extent and protect valuable residential buildings.